Permafrost Organic Carbon Mobilization From the Watershed to the Colville River Delta: Evidence From 14C Ramped Pyrolysis and Lignin Biomarkers. Issue 22 (27th November 2017) - Zhang, Xiaowen; Bianchi, Thomas S.; Cui, Xingqian; Rosenheim, Brad E.; Ping, Chien‐Lu; Hanna, Andrea J. M.; Kanevskiy, Mikhail; Schreiner, Kathryn M.; Allison, Mead A.
Abstract: The deposition of terrestrial‐derived permafrost particulate organic carbon (POC) has been recorded in major Arctic river deltas. However, associated transport pathways of permafrost POC from the watershed to the coast have not been well constrained. Here we utilized a combination of ramped pyrolysis‐oxidation radiocarbon analysis (RPO 14 C) along with lignin biomarkers, to track the linkages between soils and river and delta sediments. Surface and deep soils showed distinct RPO thermographs which may be related to degradation and organo‐mineral interaction. Soil material in the bed load of the river channel was mostly derived from deep old permafrost. Both surface and deep soils were transported and deposited to the coast. Hydrodynamic sorting and barrier island protection played important roles in terrestrial‐derived permafrost POC deposition near the coast. On a large scale, ice processes (e.g., ice gauging and strudel scour) and ocean currents controlled the transport and distribution of permafrost POC on the Beaufort Shelf. Key Points: Deposition of soil material in the river channel appeared to be more derived from deep old permafrost than surface soils Deposition of permafrost soils at the coast was affected by hydrodynamic sorting, coastal currents, and drifting ice Degradation and organo‐mineral interactions likely played important roles in the depth‐dependent thermal stability of Arctic soils